Galectin-4 is associated with diabetes and obesity in a heart failure population - Anna Dieden; Petri Gudmundsson; Johan Korduner; John Molvin; Amir Zaghi; Zainu Nezami; Erasmus Bachus; Hannes Holm; Amra Jujic; Martin Magnusson (Scientific Reports, 2023)
Abstract An association between high Galectin-4 (Gal-4) and prevalence of diabetes in subjects with heart failure (HF) has previously been reported. The purpose of this study was to confirm these findings, as well as to further investigate this association, in a Swedish HF population. In addition, a second aim was to explore Gal-4’s association with obesity and biomarkers of metabolism and heart failure. Gal-4 was measured using a proximity extension array technique in 324 hospitalized HF patients within the Swedish HeArt and bRain failure investigation trial cohort. Obesity was defined as BMI ≥ 30. Multivariable logistic regression models were used to explore associations between Gal-4 and diabetes/obesity, and linear regression models were used to explore the associations between Gal-4 and biomarkers. A total of 309 participants (29.1% female; mean age 74.8 years) provided complete data for the analysis of associations between Gal-4 and diabetes. Additionally, for the analysis of heart failure phenotype, complete data was available for 230 subjects. Gal-4 was positively associated with prevalent diabetes (OR 2.60; CI 95% 1.56–4.32). In multivariable models, Gal-4 levels were significantly associated with obesity, but only for subjects with diabetes (OR 2.48; 1.09–5.62). Additionally, Gal-4 demonstrated a significant association with the incretin Glucose-dependent insulinotropic polypeptide (GIP), as well as with biomarkers of HF. In the stratified analyses, the association between Gal-4 and diabetes was prominent in patients with reduced ejection fraction (n = 160, OR 3.26; 95%CI 1.88–5.66), while it was not observed in those without (n = 70, 1.96 (0.75–5.10)). In this cross-sectional, observational study, higher Gal-4 levels in HF patients were associated with higher GIP levels. Further, increased levels of Gal-4 were associated with increased likelihood of diabetes, and obesity. This association was particularly pronounced in individuals with HF characterized by reduced ejection fraction. Additionally, Gal-4 levels were significantly elevated in heart failure patients with diabetes and obesity.